Multi-objective based configuration optimization of SOFC-GT cogeneration plant. (5th February 2017) - Hajabdollahi, Zahra; Fu, Pei-Fang
Highlights: Thermo-economic modeling of an SOFC cogeneration plant. Considering energy, exergy, economic and environmental analyses. Applying multi-objective optimization using NSGA-II. Selecting the existence of component as design parameters. Performing the exergy destruction in each optimum equipment. Abstract: A cogeneration plant including gas turbine, solid oxide fuel cell (SOFC), heat recovery steam generator (HRSG) as well as inlet air cooling system is modeled and optimized in this work. Pressure ratio and isentropic efficiency in air compressor, gas turbine isentropic efficiency, combustion chambers exhaust temperature, absorption chiller nominal capacity, mass flow rate of steam in the chiller generator, recuperator effectiveness, inlet air cooling heat exchanger effectiveness, SOFC surface area, SOFC fuel mass flow rate as well as the existence of the each components including combustion chambers, recuperators, inlet air cooling system and SOFC are considered as design parameters. Then Genetic Algorithm for multi objective application is used to find the maximum of exergy efficiency and minimum of total cost rate, simultaneously. The results of optimization show that there is no need for inlet air cooling system for the studied case. Moreover, SOFC is needed just for a plant with higher value of exergy efficiency. Finally the trends of optimum values of five decision variables versus exergy efficiency and rate of exergy destruction in each optimum equipment are investigated and the results are reported.